Pengaruh Penerapan Gaya Mengajar Latihan Terhadap Keterampilan Gerak Dasar Pada Passing Bawah Bola Voli Siswa SMP Negeri 4 Tondano - Putry Enjeli Manampiring; A.R.J sengkey; Jan Lengkong (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2025)
This study aims to determine whether the application of the training teaching style influences the improvement of basic movement skills in underhand passing in volleyball among students at SMP Negeri 4 Tondano. This study uses an experimental method with a pre-test post-test control group design. The sample consists of 24 students, divided into two groups: an experimental group that received the training teaching style treatment and a control group that did not receive the treatment. Data were obtained through tests of basic movement skills in underhand passing in volleyball, administered during the pre-test and post-test. The results show that the experimental group, which applied the training teaching style, showed a more significant improvement in basic movement skills in underhand passing compared to the control group. Based on the t-test, the calculated t-value was greater than the table value, meaning the alternative hypothesis was accepted. Therefore, it can be concluded that the application of the training teaching style has a significant effect on improving basic movement skills in underhand passing in volleyball at SMP Negeri 4 Tondano.